Relations between the United States of America and the European Union 20031990 D- A study in the political dimension- (Journal of the College of Basic Education, 2023)
The issue of US-European relations occupied great importance in strategic studies.Especially since the development of political events stems from the apathy and strength of these relations.The success and failure of Western projects depends to a large extent on the extents of agreement and disagreement overinternational issues.At the root of these issues is the political, economic and security competition for regions.influence and expansion, and each side summoned its allies to achieve an aspect of superiority and competition, while focusingThe American side on the track of military power through NATO sought EuropeAnd France, Germany and their European allies should support it to achieve the unity of Europe to form a blocEconomic has political dimensions and the arrangement of a military security role within Europe and the world.In light of this fierce competition between the two sides, hot issues became the focus of attention.The Iraqi issue and the Middle East are among the most important issues through which the conflict can be resolved.on the world.In order to clarify a realistic and future vision of the nature of this competition and its different dimensions,Politically, economically, and in terms of security, this study came to express an important aspect of this vision.political dimensions, through which it is possible to crystallize the development trends or the conflict betweenboth parties.On this basis, our study of this topic (the relations between the United StatesAmerica and the European Union (1990-2003 (a study in the political dimension), where we discussed inThe first chapter deals with the historical roots of these relations, by presenting the nature of the relationship, whichWe found that it had passed through three stages, namely the first stage, the dependency stage, and the second stage, theindependence and the third stage, the cooperation stage. Then came the second chapter, which is the relations betweenThe United States and the European Union in the nineties with its five discussions, the first topic